MIDWIFERY CARE FOR PREGNANCY FOR MRS. P IN MT VILLAGE, SUB-DISTRICT INGIN JAYA, THE DISTRICT OF ACEH BESAR IN 2025 - Mauyah, Nizan; Husna, Asmaul; Sulastri, Sulastri (Department of Midwifery, Health Polytechnic of Aceh, 2025)
Maternal health during pregnancy is very important because it greatly affects the fetus that will soon be born. The health in question is comprehensive, encompassing the mother's physical, psychological, social, and spiritual health. Maternal Mortality Rate (MMR) is a significant indicator for assessing public health. The high maternal mortality rate indicates the low quality of health services and the lack of maternal awareness of the importance of prenatal check-ups. One of the strategic efforts to reduce MMR is the provision of quality, standardized midwifery care. The purpose of this case report is to carry out midwifery care for pregnancy in Mrs P in MP Village, Sub-district Ingin Jaya , The District of Aceh Besar, and document it in the form of SOAP. The first care was carried out on 26 March 2024. The results of the assessment showed that the mother's general condition was good, 34 weeks of gestation, with complaints of anxiety about facing labor. Physical examination and anamnesis showed results within normal limits. The care provided includes education for facing childbirth and providing emotional support, explaining childbirth to overcome anxiety, handling complaints, third-trimester discomfort, danger signs of pregnancy, teaching pregnant gymnastics, educating mothers for breast care, and explaining to mothers the signs of childbirth. The mother understands and accepts the explanation given and is willing to follow the suggested recommendations. Subsequent visits will be conducted according to the pregnancy development schedule to monitor and provide appropriate follow-up care to support a healthy pregnancy.